STRATEGI DIGITAL MARKETING UMKM DALAM UPAYA MENINGKATKAN KINERJA PENJUALAN PRODUK PASCA PANDEMI (Studi deskriptif terhadap pemilik UMKM Niekting dan Babeh Boyo) - Nur Azizah Salsabil (2023)
SME are expected to be more literate in technology in order to make it easier for MSMEs to market their products. The Covid 19 pandemic has hit the economic sector in Indonesia, many small and medium enterprises SME are struggling to deal with their hampered businesses. However, some of them were able to survive by taking advantage of the few opportunities that existed. The purpose of this study is to find out what strategies are used by MSME owners in an effort to promote a post-pandemic product. The methodology in this research is descriptive qualitative method. The data collection method of this research is by observing, interviewing, documenting, and drawing conclusions. The results of the research on the communication strategy carried out by Niekting and babeh boyo SME are through social media Instagram, by actively creating useful content, besides using a mouth to mouth strategy. The conclusion is that the communication strategy carried out by SME Niekting and Babeh Boyo is through Instagram social media by actively creating useful content, besides using a mouth to mouth strategy and also often participating in bazaars and special training